Analysis of physical conditions and basic skills of table tennis players in malang city - Nurrochmah, Siti; Furrochman, Rachmad Fariz; Firmansyah, Guntur (Universitas Suryakancana, 2022)
The purpose of this study was to determine and examine the description of the physical condition that has components which are strength, agility and reaction speed as well as basic service and drive technical skills possessed by table tennis athletes in Table Tennis Federation of Malang City. This research is a quantitative descriptive type and uses an observational test approach. The population was 55 people and the sampling used a purposive proportionate random sampling technique with a portion of 90% of 55 people, a total sample of 50 people. Data collection uses measurement techniques in the form of physical condition tests and sports skills tests. The results obtained in the components of agility, arm muscle strength, reaction speed, as well as basic drive technical skill were in the